Charleston belles abroad : the music collections of Harriet Lowndes, Henrietta Aiken, and Louisa Rebecca McCord - Bailey, Candace, 1963- (University of South Carolina Press, 2019)
An examination of the vital role music played in the lives of elite Southern women.